2021
DOI: 10.1088/1742-6596/1898/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Enhancement Forecast of Dengue Fever Outbreaks in Coastal Region

Abstract: Dengue Fever is among the world’s fastest-spreading mosquito-borne illnesses. In Indonesia, more than 33 percent of the world community is in danger. The Coastal Zone is one of the region most at risk of contracting dengue fever, particularly from the social and environmental sectors, so an early diagnostic study must deal with this efficiently and effectively. This research aimed to predict and identify the coastal areas with the most severe dengue fever potential to avoid dengue fever. The methodology used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…According to the findings of studies which have included wind speed, one study has revealed that low wind speed prevents dengue outbreak (Ahmed & Siddiqui, 2014) while another study has found a strong correlation between wind speed and DHF incidence (Minarti et al, 2021). In contrast, five studies included in the review have concluded that there is no correlation between wind speed and DHF incidence or dengue cases (Arsin et al, 2020;Harumy & Ginting, 2021;Noppradit et al, 2021;S. A. Rahman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the findings of studies which have included wind speed, one study has revealed that low wind speed prevents dengue outbreak (Ahmed & Siddiqui, 2014) while another study has found a strong correlation between wind speed and DHF incidence (Minarti et al, 2021). In contrast, five studies included in the review have concluded that there is no correlation between wind speed and DHF incidence or dengue cases (Arsin et al, 2020;Harumy & Ginting, 2021;Noppradit et al, 2021;S. A. Rahman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding has found to be statistically not significant (r= 0.76, p=0.492) (Minarti et al, 2021). Apart from the above findings, five studies included in the review have concluded that there is no correlation between wind speed and DHF incidence or dengue cases (Arsin et al, 2020;Harumy & Ginting, 2021;Noppradit et al, 2021;S. A. Rahman et al, 2018).…”
Section: Impact Of Wind On Denguementioning
confidence: 94%
See 2 more Smart Citations